2016
DOI: 10.1016/j.archoralbio.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide promotes osteogenic differentiation of human periodontal ligament cells via p38-MAPK signaling pathway under proper tension stimulation

Abstract: HS could promote osteogenic differentiation of hPDLCs by activating p38-MAPK and ERK signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Other non-collagenous proteins, such as laminin 5 and matrix protein 3, can induce the expression of Cbfa-1 and ALP through the ERK1/2 signaling pathway and can enhance the matrix mineralization and osteogenic differentiation of hMSCs. 408 Together, these results suggest that the MAPK signaling pathway plays an important role in the osteogenic differentiation of hMSCs.…”
Section: Interactions Between Bone Biomaterials and Stem Cellsmentioning
confidence: 80%
“…Other non-collagenous proteins, such as laminin 5 and matrix protein 3, can induce the expression of Cbfa-1 and ALP through the ERK1/2 signaling pathway and can enhance the matrix mineralization and osteogenic differentiation of hMSCs. 408 Together, these results suggest that the MAPK signaling pathway plays an important role in the osteogenic differentiation of hMSCs.…”
Section: Interactions Between Bone Biomaterials and Stem Cellsmentioning
confidence: 80%
“…Then, we investigated how POSTN improves migration and osteogenic differentiation of PDLSCs under inflammatory conditions.Previous studies have reported that POSTN promotes cell mobility, adhesion and survival in a number of cell types by binding to integrin αvβ3 and αvβ5 via focal adhesion kinase (FAK) phosphorylation and AKT phosphorylation in the integrin-mediated signalling pathway [23][24][25]. According to previous research, the differentiation and inflammatory response of PDLSCs or PDL cells could be affected through the P38 and ERK1/2 signalling pathways by a number of stimulatory factors [31][32][33][34]. Additionally, our previous study found thatPOSTN acted on PDLSCs via the integrin signalling pathway; the integrin inhibitor Cilengitide represses POSTN-enhanced cell migration.…”
mentioning
confidence: 99%
“…Our previous in vitro study also demonstrated that H 2 S could promote osteogenic differentiation by up-regulating the expression ratio of OPG/RANKL expression in human PDLSCs ( 18 ). It was also demonstrated that H 2 S significantly increased the expression of ALP, OCN, runt-related transcription factor 2 and collagen 1 in the human PDLSCs with tension force stimulation, and promoted osteogenic differentiation of human PDLSCs by activating the p38-MAPK and ERK signaling pathways ( 19 , 35 ). In the present study, exogenous H 2 S could up-regulate the expression of ALP and OCN, the ratio of RANKL/OPG and the number of osteoclasts in the alveolar bone.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, exogenous H 2 S could up-regulate the expression of ALP and OCN, the ratio of RANKL/OPG and the number of osteoclasts in the alveolar bone. ALP has been commonly studied as an early marker of osteogenic differentiation in tension force experiments and OCN is a key transcription factor in the modulation of osteogenic differentiation and bone formation ( 19 ). The results of the present study revealed that H 2 S could up-regulate the process of osteogenesis, osteoclastic activities and bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation